(untitled) (KASBIT Business Journal, 2022)
This study attempts to investigate the prediction power of capital adequacy ratios about banking distress. Taking commercial banks from Pakistan as a study sample for a period from 2011 to 2020, this study highlights the role and importance of the capital adequacy ratio in the prediction of banking distress. The research findings conclude that capital adequacy ratios are the sources that signal the banking soundness in emerging economies and financial distress in banking can be predicted by alternative capital ratios. The study recommends that commercial banks must have to develop and adopt regulatory and reporting structures on capital adequacy to safeguard themselves from the unexpected risk of default. Further, banking officials are also advised to maintain a steady capital ratio to avoid potential losses from insufficient liquidity capital.